PENERAPAN PEMBELAJARAN KOOPERATIF BERBASIS MASALAH DENGAN MODEL JIGSAW UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN SEJARAH INDONESIA KELAS XI DI SMAN 4 PRAYA TAHUN PELAJARAN 2018-2019 - sarjana, akhmad (FAJAR HISTORIA: Jurnal Ilmu Sejarah dan Pendidikan, 2018)
The purpose of this study was to explain the application of problem-based cooperative learning with a jigsaw model to improve student achievement in class XI at SMAN 4 Praya Academic Year 2018-2019. The results showed that the application of Problem Based Cooperative Learning with the Jigsaw Model made: First, improve the performance of teaching staff in the material that the Development of Imperialism and Westhern Colonialism in each cycle. Second, increasing students in the learning process in globalization material in each cycle. Third, Increase the average student learning outcomes in the material Development of Imperialism and Westhern Colonialism in each cycle